Avoiding Double Taxation through the Assessment of International Tax Treaties. Case: ESP's versus ANAF Brașov (Journal of Legal Studies, 2019)
International double taxation represents one of the main problems’ for which taxpayers have to deal within a world fulfilled with globalization, uncertainty, risk, asymmetrical information and moral hazard. In this sense, in this article it is provided a qualitative overview regarding the appearance and evolution of the main double taxation conventions and their legal framework. In this article it is tackled some important issues, namely: the rationale behind the construction and engaging in double taxation conventions; the need for a coherent and just application of those conventions; the historical appearance and evolution of the double taxation conventions, as well as the quid pro quo OECD Model Convention and UN Model Convention. The conclusions of this article highlight the importance and ultimately need for construction of best practices new and complex multilateral tax convention at the UE level in order to diminish the contagious effects of the treaty shopping practices. The case study presented in this article from the Romanian jurisprudence highlights the multi-faced concept of double taxation and the comprehension approach which must be undertaken in order to solve the complex issues of the international taxation via double taxation treaties.